Peran Koperasi Syariah dalam Membebaskan Anggota dari Jeratan Riba - Adi Prawira (Saqifah: Jurnal Hukum Ekonomi Syariah, 2023)
Sharia Cooperatives are Islamic financial institutions that carry out their activities no different from conventional financial institutions, the difference lies in the principles and laws used, where Islamic cooperatives must comply with Islamic law and implement Islamic sharia principles. One of the sharia principles is that the transactions used in Islamic cooperatives must be free from riba. One of the problems is that members still have loans to conventional financial institutions, and have a desire to be able to avoid riba transactions, so cooperative members must take over debt to no ribawi institutions.  Islamic cooperatives can provide sharia-based financing alternatives. One of the contracts that can be used in take over debt from conventional financial institutions to Islamic cooperatives is a debt transfer contract. This debt transfer is carried out based on the Fatwa of the Indonesian Sharia Council of the Indonesian Ulema Council No. 31/DSN-MUI/VII/2002. This DSNI MUI Fatwa in take over debt provides four alternatives. By following the DSN MUI Fatwa, customers can take over debt from conventional institutions to Islamic cooperatives to avoid riba.